A educação na fronteira entre museus e escolas: um estudo sobre as visitas escolares ao Museu Histórico Abílio Barreto - Soraia Freitas Dutra (2012)
The aim of this work is to analyse the relationship between museum and school, that is, how these social spaces of educational experiences interact. It also intends to show how these two environments and their respective actions upon individuals can contribute to citizens cultural development. The movement from the school universe to the museum is considered as a space/time of hybrid learning that is produced through the links of references between these two universes and, therefore, imbued with cultural differences. According to our analysis, the movement from the school to the museum can be seen not only as an exchange of environments but also as a movement of cultural references. Thus, school visits to the museum can be seen as intercultural displacements that can mobilize elements of both cultural contexts. From the beginning of the 90s up to now we have analysed the educational experiences developed in Abílio Barreto Historical Museum (BH-MG) concerning school visits to this cultural environment. We also analysed the uses and ways of building knowledge about the museum environment by the school in 2009. Our research consisted of two distinct and complementary periods: a diachronic and a synchronous analysis of the educational experiences in the museum in relation to the school environment. The process of collecting data in the museum was also divided into three periods: a documentary research (1stperiod) and an ethnographic research(2nd period). In order to take the school universe into account we carried out interviews with the teachers who visited Abílio Barreto in 2009 (3nd three). Taking into account concepts such as culture (GEERTZ; SHALINS; GREEN; GOMES), school culture (JÚLIA), years of school attendance and school experiences (FARIA FILHO; VIDAL), museum culture (MARANDINO, NASCIMENTO), experiences(DE CERTEAU), uses and knowledge building (DE CERTEAU, CHARTIER), all the analyses show the school visits to the museum as an experience that establishes a hybrid educational experience which can ultimately promote the learning of culture.